Making a Difference: Affective Distress Explains Discrepancy Between Objective and Subjective Cognitive Functioning After Mild Traumatic Brain Injury. Issue 3 (May 2021) - Hromas, Gabrielle A.; Houck, Zachary M.; Asken, Breton M.; Svingos, Adrian M.; Greif, Sarah M.; Heaton, Shelley C.; Jaffee, Michael S.; Bauer, Russell M.
Abstract : Objective: To assess the relationship between subjective cognitive symptoms and objective cognitive test scores in patients after concussion. We additionally examined factors associated with subjective and objective cognitive dysfunction, as well as their discrepancy. Participants: Eighty-six individuals (65.1% female; 74.4% adult) from an interdisciplinary concussion clinic. Methods: Subjective and objective cognitive functioning was measured via the SCAT—Symptom Evaluation and the CNS Vital Signs Neurocognition Index (NCI), respectively. Cognitive discrepancy scores were derived by calculating standardized residuals (via linear regression) using subjective symptoms as the outcome and NCI score as the predictor. Hierarchical regression assessed predictors (age, education, time postinjury, attention-deficit/hyperactivity disorder, affective distress, and sleep disturbance) of cognitive discrepancy scores. Nonparametric analyses evaluated relationships between predictor variables, subjective symptoms, and NCI. Results: More severe affective and sleep symptoms (large and medium effects), less time postinjury (small effect), and older age (small effect) were associated with higher subjective cognitive symptoms. Higher levels of affective distress and less time since injury were associated with higher cognitive discrepancy scores (β = .723, P < .001; β = −.204, P < .05, respectively). Conclusion: Clinical interpretation of subjective cognitive dysfunction should consider these additional variables. Evaluation of affective distress is warranted in the context of higher subjective cognitive complaints than objective test performance.